Virtual reality simulator for vitreoretinal surgery using integrated OCT data - Kozak I (Dove Medical Press, 2014)
Igor Kozak,1 Pat Banerjee,2 Jia Luo,2 Cristian Luciano21King Khaled Eye Specialist Hospital, Vitreoretinal Division, Riyadh, Kingdom of Saudi Arabia; 2College of Engineering, University of Illinois at Chicago, Chicago, IL, USAAbstract: Operative practice using surgical simulators has become a part of training in many surgical specialties, including ophthalmology. We introduce a virtual reality retina surgery simulator capable of integrating optical coherence tomography (OCT) scans from real patients for practicing vitreoretinal surgery using different pathologic scenarios.Keywords: optical coherence tomography